Combined impact of ultraviolet radiation and increased nutrients supply: a test of the potential anthropogenic impacts on the benthic amphipod Amphitoe valida from Patagonian waters (Argentina) - Valiñas, Macarena S.; Bermejo, Paula; Galbán, Lara; Laborda, Luciana; Häder, Donat-P.; Villafañe, Virginia E.; Helbling, E. Walter (Frontiers in Environmental Science, 2014)
Experiments were conducted during the Austral Summer of 2014 to determine the effects of increased nutrient input and ultraviolet radiation (UVR) on the food consumption rate (FCR) and food preference in the amphipod Amphitoe valida. We collected specimens from the Patagonian coast (Argentina), from beaches close (Barrancas Blancas; BB) and further away (Cangrejales; C) from the Chubut River, which constitutes the potential source of eutrophication. Organisms were exposed to different radiation regimes (full radiation vs. PAR only) and fed with different macroalgae diets (i.e., from different geographical location and with different quality in terms on nutrient content). Males collected from C showed food compensation, consuming more food under low-nutrient diets, while no compensation was observed in males from BB. Regardless of their origin, UVR decreased the FCR when males where fed on ambient nutrient diets, but not when males fed on high-quality diets indicating that in the former case, individuals were in worse physiological conditions to cope with UVR; food quality, however, significantly counteracted the deleterious effects of UVR on FCR. Females collected from the two beaches showed similar FCR under high-nutrient diet and had no food compensation when fed in low-nutrient diets. Females were more vulnerable to UVR, since their FCR were lower when exposed to UV radiation independent of the diet. Our results show that under anthropogenic eutrophication and high solar UVR levels an increase in the nutrient input could favor only males of A. valida, by reducing the negative effects of UVR on their FCR. Nevertheless, these nutrient inputs might cause additional problems like anoxia, as a result of an unusual macroalgal growth, thus affecting amphipod’s survival.